Adjuvant treatment delay in breast cancer patients - Trufelli,Damila Cristina (2015)
Summary Background: to evaluate if time between surgery and the first adjuvant treatment (chemotherapy, radiotherapy or hormone therapy) in patients with breast cancer is a risk factor for lower overall survival (OS). Method: data from a five-year retrospective cohort study of all women diagnosed with invasive breast cancer at an academic oncology service were collected and analyzed. Results: three hundred forty-eight consecutive women were included. Time between surgery and the first adjuvant treatment was a risk factor for shorter overall survival (HR=1.3, 95CI 1.06-1.71, p=0.015), along with negative estrogen receptor, the presence of lymphovascular invasion and greater tumor size. A delay longer than 4 months between surgery and the first adjuvant treatment was also associated with shorter overall survival (cumulative survival of 80.9% for delays ≤ 4 months vs. 72.6% for delays > 4 months; p=0.041, log rank test). Conclusion: each month of delay between surgery and the first adjuvant treatment in women with invasive breast cancer increases the risk of death in 1.3-fold, and this effect is independent of all other well-established risk factors. Based on these results, we recommend further public strategies to decrease this interval.